ANALYSIS OF ACCOUNTS RECEIVABLE AND CASH MANAGEMENT ON HOSPITAL OPERATING CASH FLOW IN THE JKN ERA: A LITERATURE REVIEW - Yeyen Iscasari; Dimas Aqiel Baihaqi P; Nur Eka Sanfitri; Budi Hartono (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
The National Health Insurance (Jaminan Kesehatan Nasional or JKN) era has changed hospital financing patterns, particularly through the claim mechanism submitted to BPJS Kesehatan. Under this system, hospitals are highly dependent on the smooth process of claim submission, verification, and payment. However, several problems are still frequently found in practice, such as delayed claim payments, pending claims, claim disputes, and weak receivables and cash management. These conditions may disrupt the stability of hospital operating cash flow, especially in financing health services, medicines, medical supplies, service fees, and daily operational needs. This article aims to analyze the role of receivables management and cash management in supporting the smooth flow of hospital operating cash in the JKN era. The method used is a narrative literature review by examining relevant journal articles, regulations, official reports, and scientific publications. The reviewed literature was published between 2015 and 2025 and obtained from Google Scholar, Garuda Kemdikbud, Neliti, DOAJ, and government regulatory portals. The search keywords included hospital receivables management, BPJS receivables, pending BPJS claims, hospital cash management, hospital operating cash flow, JKN, INA-CBG, and related terms. The findings show that receivables and cash management play an important role in maintaining hospital cash flow stability. BPJS receivables that are not collected on time may cause liquidity constraints. Therefore, hospitals need to strengthen receivables aging monitoring, pending claim settlement, claim audits, staff competency, system digitalization, and periodic cash flow projections.